GROW-OUT OF ABALONE Haliotis squamata IN FLOATING CAGES FED DIFFERENT PROPORTIONS OF SEAWEED AND WITH REDUCTION OF STOCKING DENSITY - I Nyoman Adiasmara Giri; Tatam Sutarmat; Hirmawan Tirta Yudha; Ibnu Rusdi; Bambang Susanto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Abalone is a herbivore marine animal which feeds on seaweed. Abalone culture has a good prospect in terms of price, market share and simple culture technique. Thus, a study was conducted with the aim of finding out an effective and efficient abalone culture technique in terms of feed use and density. In this study, a 42 cm diameter plastic container with a 22 cm height was used. Three vertically arranged containers were used as the experimental group which were put into a net box and hung onto a raft so that the containers were placed in a 4 m depth below the sea surface. The juvenile of abalones being used came from a hatchery production that has been adapted to cages environment with Gracilaria sp. and Ulva sp. feed. The initial density of abalones was 450 for each container, with the initial weight of 2.6-3.2 g and the 2.5-2.7 cm shell lengths. The abalones were fed with Gracilaria sp. and Ulva sp. seaweeds with different Gracilaria sp./Ulva sp. proportions, i.e. 100/0% (A); 80/20% (B); and 60/40% (C) as the treatments. Each treatment consisted of two replications. After three months of rearing period, densities of abalones were reduced to be 190 for each experimental unit. Weight and shell length of abalones were measured every month by measuring 25 abalone samples from each experimental unit. The result of the experiment showed that the increase in the Ulva sp. proportion in the feed increased the growth of abalones and decreased the feed conversion. Feeding with Gracilaria sp./Ulva sp. proportion of 60%/40% allowed the best growth of abalones. The decrease of abalone density in the experimental unit after three months of rearing also produced an increase in their growth.